A Systematic Comparative Assessment of Certification Standards in India and Suggested Evaluation Frameworks - Verma, Madhu; Sharma, Parul; Joe, Elphin Tom (Frontiers in Sustainable Food Systems, 2022)
Sustainable agriculture has the potential of addressing major social and environmental challenges affecting agriculture in India. One of the ways to promote sustainable agriculture is through certification. This refers to the broad family of voluntary standards set by third-party against which producers are independently audited and certified. An appropriate sustainability framework can guide more effective food procurement by accounting for context in the form of demand architecture and production systems. The paper therefore presents a review of five different sustainability certifications prevalent in India with focus on spice certification. These have been analysed against value drivers, impact pathways to different capitals, sustainability issues and the stakeholders involved. The results indicate that these certifications cover mostly common issues with no evident differences indicating the possibility for a need for differentiation to let consumers choose based on their preferred concerns. An evaluation framework is prepared to make a case for evaluating these certification initiatives to outline the differential parameters.